Sustainable Herbal Medicine Tourism Village: Integration of Local Wisdom, Ecotourism, and Empowerment of Herbal Farmers - Djati, Muhammad Sasmito; Christina, Yuyun Ika; Annisa, Yuslinda; Azmi, Shella Zahra Kumala; Dwijayanti, Dinia Rizqi; Tyasmoro, Setyono Yudo; Zubaidah, Elok; Hakim, Luchman (Journal of Innovation and Applied Technology, 2026)
Indonesia is a tropical country with rich biodiversity that supports the growth of a wide variety of medicinal plants. For generations, these plants have been used in traditional healing and are embedded in community culture, while also offering strong potential for developing herbal products such as jamu and phytopharmaca. This program aimed to empower jamu farmers and Asman Toga groups in Ngroto Village, Pujon Subdistrict, Malang Regency, by integrating local knowledge and ecotourism concepts to initiate a sustainable “Jamu tourism village”. The approach combined participatory training, hands-on assistance to develop locally sourced jamu products, and enhanced marketing skills. The activities resulted in improved capacity among jamu farmers and Asman Toga groups to innovate jamu-based products and raised broader community awareness of the potential of jamu-based tourism. The integration of local wisdom and ecotourism strengthened Ngroto’s identity as an emerging destination for jamu education and experiences.